A study of the factors influencing advertising avoidance in the context of Chinese social media - Liang, Yingjun (2022)
With the constant innovation of internet technology, social media is growing rapidly and has gradually become an important medium for people to socialise and obtain information and entertainment. These multi-functional platforms have massive users and an amazing speed of information dissemination, attracting marketers to invest time, money and resources in them to post advertisements. Social media newsfeed advertising is a key part of social media advertising and is heavily placed in users' content streams. Although these ads are similar to regular posts, they are still recognisable to users, and advertising avoidance still exists. With social media allowing users more power to reject commercial ads, users have become more adept at avoiding them. It has somewhat affected marketers' advertising promotions and business models conducive to social media platforms' long-term development. Most research on advertising avoidance is conducted in traditional and Web 2.0-based Internet environments, with little research on advertising avoidance in the context of social media. And the existing models of social media advertising avoidance do not consider the unique social characteristics of social media and social media advertising.